Toward an Improved Shared Understanding of TNE - Ilieva, Janet; Ramos, Eduardo; Peak, Michael (International Higher Education, 2024)
Transnational education (TNE) has experienced significant growth recently, with more students enrolling in TNE programs and more institutions involved in TNE. This article develops a framework that captures the impacts of TNE on local education systems and explores the host country’s perspective on TNE. TNE is crucial in bridging the gap between supply and demand for higher education, supporting access for disadvantaged groups, and capacity building. It supports nations’ aspirations for an international student hub.